Jak długo judaizm postrzegany był jako superstitio w pogańskim Imperium Romanum - Kowalczyk, Anna (Acta Universitatis Lodziensis. Folia Historica, 2014)
The emergence of the Jewish community in Rome in the second century B.C. initiated an elaborate dialogue of the Jews and the Romans who were forced to confront not only a different type of religion but also very different customs and traditions. Dissimilarity of the Jews made them incomprehensible to the pagans and a feeling of resentment aroused due to the lack of participation in worship or circumcision. For this reason Judaism was recognized as superstitio. Religious liberty granted to the Jews by Julius Caesar and Augustus began a long process of changing the way Judaism and its followers were perceived. However it did not mean immediate acceptance of the Jewish community, what was particularly evident during the reign of Tiberius, when he expelled them from Rome. In the following years manifestations of hostility towards Jews were especially visible in Alexandria, where a pogrom took place. Usually the action directed against the followers of Judaism occurred because of violations of order in the empire, just like during the first Jewish War. The main motive behind the decisions of the Roman authorities was the suppression of riots and not persecution because of religious differences. Subsequent Jewish revolts against Roman authorities also did not lead to depriving them of religious freedom. Moreover, while the Christian faith was banned during the reign of Trajan, the Jews had permission to practice their religion. Even during the persecution of Christians under Diocletian, the Jewish community was exempt from the obligation to participate in worship, which meant that Judaism was no longer considered dangerous to the old gods, and thus ceased to be superstitio.